Surface modification of 316L Stainless Steel alloy using Nano Ceramic Hydroxyapatite, Magnesium Oxide, Zinc Oxide, and composite coating by EPD to enhancing corrosion resistance in biomedical application - Hazber, Aya Muhsin; Jasim, Ayad Naseef; Al-Bawee, Abbas (Al-Nahrain Journal for Engineering Sciences, 2026)
The toxicity of permanent implants is the main concern. The release of ions from the substrate leads to toxicity. Because of how the human body works biologically, the toxicity of corrosion compounds is a byproduct of wear and fretting debris. aimed to improve the corrosion resistance of a 316L stainless steel substrate. Bio ceramic Nano-hydroxyapatite (HA) was coated using the Electrophoretic Deposition (EPD) technique. Stainless steel has good mechanical properties and high compatibility, but it suffers from body fluid attack due to its chloride content, which can penetrate the passivation layer, resulting in the release of chromium and nickel ions. Tissues and organs are damaged by the ions and debris that are released. To address this problem, it was coated with bioceramic using the EPD method. Suspensions of various powders—hydroxyapatite, magnesium oxide, zinc oxide, and the composite—were prepared and coated by electrophoretic deposition. The coated samples were dried at room temperature to ensure a homogeneous coating structure. The zeta potential test for magnesium oxide and hydroxyapatite suspensions was positive, while zinc oxide and complex suspensions were negative. One of the important parameters for achieving electrolyte and implant balance is the open circuit potential (OCP). A substantial change towards a more noble direction (less negative) was seen in the OCP-coated (316 L) alloy, suggesting excellent thermodynamic stability. Tafel extrapolation analysis was used to obtain the corrosion potential (Ecorr) and corrosion current density (Icorr) values of composite-coated stainless steel 316L, which are generally derived from the polarization curve. The findings that are in line with the MgO, HA, and ZnO coatings show a significant decrease in corrosion current (Icorr), an increase in corrosion potential (Ecorr), and a decrease in corrosion rate from (4.386 × 10-¹ mm/y) Stainless Steel 316 L to (1.417 × 10-² mm/y) MgO Coated and (1.222 × 10-³ mm/y) (65%MgO+25%ZnO+10%HA coated).